Organizational innovations and access to sustainable finance in agriculture: the case of Shea farmers in Ghana - Ramoudane Orou Sannou; Christian P. Schneider; Matthias Walz; Edeltraud Guenther (International Journal of Agricultural Sustainability)
Access to finance is essential for sustainable agriculture and improving rural livelihoods. This study examines the impact of organisational innovations and sustainable finance accessibility on the livelihoods of rural women. Our research focuses on 50 female Shea nut producers in Kpugi, northern Ghana, who are beneficiaries of the ‘Invest for Jobs’ initiative. Using a mixed-methods approach and case study research, data were gathered through focus group discussions and interviews with members of two cooperatives. The findings reveal that while cooperatives facilitate access to finance, they should be viewed as part of a broader package of organizational innovations rather than standalone solutions. The success of the cooperatives owes to the deep cultural roots of Shea farming in the lives of the women, making it easy for them to accept innovations that will improve their success in an activity they do not plan to abandon. Increased bargaining power and subsequent income increase result not only from delayed selling, stemming from finance access but also from improved production practices and better storage infrastructure. This paper highlights how a package of organisational innovations can catalyse women’s financial inclusion and emphasises the importance of nurturing such innovations within activities deeply rooted in rural livelihoods.